The four-quadrant phase-mask coronagraph: white light laboratory results with an achromatic device - Mawet, D.; Riaud, P.; Baudrand, J.; Baudoz, P.; Boccaletti, A.; Dupuis, O.; Rouan, D. (Astronomy and astrophysics (Berlin), 2006)
Achromatic coronagraphs are the subject of intensive research since they will be mandatory for many programs which aim at detecting and characterizing exoplanets. We report a laboratory experiment assessing the performance of the Four-Quadrant Phase-Mask coronagraph (FQPM) over a broadband wavelength range ($R≈ 2$). The achromatization of the FQPM is provided by achromatic halfwave plates (HWP). These phase shifters combine birefringent plates made of different materials with properly chosen thicknesses. The HWP thickness control is relaxed by two orders of magnitudes with respect to the classical (non-birefringent) dispersive plate approach. In our experiment we used a two stage stack of Quartz and MgF2. This combination allows to cover a large spectral range in the visible ($500{-}900\, \rm nm$) with a small phase error residual around π ($≈ $0.12 rad rms). With this achromatization, we obtained an attenuation of 755 on the white light PSF peak. This solution is directly applicable to ground-based telescopes using high order adaptive optics such as the ESO's VLT-Planet Finder project and could easily be transposed in the mid-infrared domain for future space-based missions like DARWIN/TPF.